The roles of free oxygen radicals, nitric oxide, and endothelin in caustic injury of rat esophagus - DAĞLI, EMRULLAH TOLGA; KIYAN, GÜRSU; YÜKSEL, MERAL (W B SAUNDERS CO-ELSEVIER INC, 2004)
Purpose: The authors aimed to find out the roles of free oxygen radicals, nitric oxide (NO), and endothelin (ET) in caustic injury of rat esophagus. Methods: Forty-five Wistar albino rats were used to form 6 groups. The study groups are summarized as 1, sham (S; n = 7); 2, sham + L-arginine (SA; n 7); 3, sham + L-NAME (SN; n = 7); 4, injury (I; n = 8); 5, injury + L-arginine (IA; n = 8); 6, injury + L-NAME (IN; n = 8). Normal saline in the sham groups and 50% NaOH in the caustic injury groups were administered to the distal esophagus. Free oxygen radicals and NO were detected by chemiluminescence from tissue samples, and they were correlated with histologic examinations. Tissue ET was measured also with immunohistochemistry. Results: The injury was verified histologically. Free oxygen radical levels were found to be increased as well as NO and ET with the caustic injury (P < .05). L-arginine caused a histologic increase in the injury that was close to statistical significance (P = .08). L-NAME showed no significant effect. Conclusions: Free radicals, NO, and ET increase in the early phase of caustic esophageal injury. Understanding their early interactions during the caustic injury may help in future therapeutic strategies. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: caustic esophagitis; free oxygen radicals; nitric oxide; endothelin; BURNS; CORTICOSTEROIDS; INHIBITION; CHILDREN; RELEASE; TRIAL